S-layer fusion protein as a tool functionalizing emulsomes and CurcuEmulsomes for antibody binding and targeting - Üçışık, Mehmet; Küpçü, Seda; Breitwieser, Andreas; Gelbmann, Nicola; Schuster, Bernhard; Sleytr, Uwe (Elsevier, 2015)
Selective targeting of tumor cells by nanoparticle-based drug delivery systems is highly desirable because it maximizes the drug concentration at the desired target while simultaneously protecting the surrounding healthy tissues. Here, we show a design for smart nanocarriers based on a biomimetic approach that utilizes the building principle of virus envelope structures. Emulsomes and CurcuEmulsomes comprising a tripalmitin solid core surrounded by phospholipid layers are modified by S-layer proteins that self-assemble into a two-dimensional array to form a surface layer. One significant advantage of this nanoformulation is that it increases the solubility of the lipophilic anti-cancer agent curcumin in the CurcuEmulsomes by a factor of 2700. In order to make the emulsomes specific for IgG, the S-layer protein is fused with two protein G domains. This S-layer fusion protein preserves its recrystallization characteristics, forming an ordered surface layer (square lattice with 13 nm unit-by-unit distance). The GG domains are presented in a predicted orientation and exhibit a selective binding affinity for IgG.
WOS: 000353930000019
PubMed ID: 25734967
Keywords: Emulsomes; Curcumin; S-layer (fusion) Proteins; Immunoglobulin G (IgG) Targeting; Active Drug Delivery